Pasang Surut Kesenian Kuda Kosong Cianjur Tahun 1998-2011 - Jamilah, Neng Mala; Yulifar, Leli (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
This research is entitled “Kuda Kosong Art of Cianjur (1998-2011) (Study of Traditional Art in The Global Flow)”. The reason behind this research is the fact that the art of Kuda Kosong in Cianjur District was once banned, then reappeared and the lack of writings or studies on local history, especially about Kuda Kosong in Cianjur District. So this research focuses on the development of Kuda Kosong art in 1998-2011 in Cianjur District. This study aims to obtain information about the ebb and flow of Kuda Kosong art in Cianjur District. This study aims to obtain information about the ebb and flow of the Kuda Kosong art in Cianjur District. The method used in this research is historical method consisting of several steps that includes the collection of the source material, verification or criticism regarding the source of research, and historiography or written history. The results of the Kuda Kosong art research in Cianjur District include information that this art has existed since the 18th century in Cianjur District. The development of Kuda Kosong art experiences ups and downs and there is a change in function, namely kuda kosong art can be addressed publicly which at first can only be witnessed by guests of the pavilion. The procession of ngalinggihkeun and ngalungsurkeun in Kuda Kosong art was eliminated because it was considered not in accordance with Islamic law. As a result, it hampered the development of the Kuda Kosong art in 1998. Efforts to preserve the kuda kosong art, the government collaborated with various parties involved, namely artists, cultural observers, and MUI so that the Kuda Kosong art could be performed again with the condition that some deviant processions were eliminated.